KETERKAITAN BAHASA DAN LOGIKA DALAM BERPIKIR KRITIS - - Warsiman (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2011)
The purpose of this study is to analyze relation between language and logic in thinking critically by some stages. Some of them are: explanation about language performance which is started by reception and perception continued with the expression of mind, memory and language memory. Then input stage, storing stage, and output stage. The next explanation are logic as think science, logical barrier, basic principles on logic, thinking critically as an ability requires to get knowledge. Knowledge is getting through scientific method. Scientific method is the way of how mind works. Trough that way production of knowledge hopefully has particular characteristics which demanded by scientific knowledge that are logical and tested. In order to reach the aims, scientific method should combines deductive ways in thinking to develop the knowledge.